2007
DOI: 10.1016/j.janxdis.2006.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Visually induced postural sway in anxiety disorders

Abstract: Postural sensitivity to moving visual environments in patients with anxiety disorders was studied. We hypothesized that patients with anxiety disorders would have greater sway in response to a moving visual environment compared to healthy adults, especially if they have space and motion discomfort (SMD). Twenty one patients with generalized anxiety without panic (NPA), and 38 patients with panic and agoraphobia (PAG) were compared to 22 healthy controls. SMD was evaluated in all subjects via questionnaire. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 37 publications
3
59
1
1
Order By: Relevance
“…[39] Our results also support the claim that patients with anxiety and SMD rely more heavily on visual cues for postural control. [8] Jacob and coworkers [14] also found that disorientation sensitivity was related to postural instability, and it is likely that postural instability precedes body symptoms, in a process similar to that seen in motion sickness. [40] BODY SYMPTOMS Postural control relies on multisensory processing and motor responses that seem to be automatic and occur without conscious awareness.…”
Section: Space and Motion Discomfortmentioning
confidence: 96%
See 1 more Smart Citation
“…[39] Our results also support the claim that patients with anxiety and SMD rely more heavily on visual cues for postural control. [8] Jacob and coworkers [14] also found that disorientation sensitivity was related to postural instability, and it is likely that postural instability precedes body symptoms, in a process similar to that seen in motion sickness. [40] BODY SYMPTOMS Postural control relies on multisensory processing and motor responses that seem to be automatic and occur without conscious awareness.…”
Section: Space and Motion Discomfortmentioning
confidence: 96%
“…[8] Unfortunately, the tendency to regard these disorders as related has lead to patients with differing specific disorders being lumped together, making it difficult to ascertain the selective effects of factors such as balance control. There are, in fact, several good reasons for thinking that acrophobics may struggle with postural control.…”
Section: Introductionmentioning
confidence: 99%
“…Visual-vestibular conflict and optokinetic stimulation have been used as intervention strategies for vestibular rehabilitation [38,39,40,4]. However, in this study optokinetic stimulation conditions did not trigger augmented destabilising effects, therefore exposure to optokinetic stimulation may not be an appropriate intervention in rehabilitation for older people at increased risk of falls.…”
Section: Discussionmentioning
confidence: 73%
“…It increases with age [1] and is prevalent not only in older people [2] but also in those with vestibular and anxiety disorders [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation